2018
DOI: 10.1002/jsfa.8897
|View full text |Cite
|
Sign up to set email alerts
|

Effects of washing, soaking and domestic cooking on cadmium, arsenic and lead bioaccessibilities in rice

Abstract: Washing and cooking of rice lowered the health risk by reducing Cd, As and Pb concentrations and bioaccessibilities respectively. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Rice cooking methods (normal cooking, high‐pressure cooking, and microwave cooking) were performed by our previous study (Liu, Zheng, & Chen, ), which based on Chinese national standard and common cooking methods in Asia. In addition to above cooking operations, rice samples were also cooked in reducing agent (0.1 M 2‐mercaptoethanol) and ionic/nonionic detergents (2% Triton X‐100 and 2% CHAPS), respectively, in order to explore any effect of disulfide bonds or hydrophobic interactions during rice cooking on protein digestibility.…”
Section: Methodsmentioning
confidence: 99%
“…Rice cooking methods (normal cooking, high‐pressure cooking, and microwave cooking) were performed by our previous study (Liu, Zheng, & Chen, ), which based on Chinese national standard and common cooking methods in Asia. In addition to above cooking operations, rice samples were also cooked in reducing agent (0.1 M 2‐mercaptoethanol) and ionic/nonionic detergents (2% Triton X‐100 and 2% CHAPS), respectively, in order to explore any effect of disulfide bonds or hydrophobic interactions during rice cooking on protein digestibility.…”
Section: Methodsmentioning
confidence: 99%
“…A third category of mitigation relies on rice cooking methods. Washing and/or cooking in excess water reduce rice grains’ As content [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Among limited studies, Sengupta et al(2006) examined the effect of soaking and washing on rice in reducing arsenic and reported 28% reduction by sequential wash of rice in water (1:5 ratio) up to reach a clear water. Similarly, it was reported that washing significantly reduced the concentration of arsenic, cadmium and lead (Liu et al, 2018).…”
Section: Introductionmentioning
confidence: 76%
“…Digestion of samples was conducted according to method described by Liu et al (2018) with modifications. The microwave vessels (Multiwave 3000, Rotor 8NXQ80, Anton Paar, Austria) were cleaned with nitric acid followed by washing with ultra-pure water.…”
Section: Heavy Metals Analysismentioning
confidence: 99%
See 1 more Smart Citation